1974
DOI: 10.2307/2347133
|View full text |Cite
|
Sign up to set email alerts
|

Biases in Local Government Elections Due to Position on the Ballot Paper

Abstract: Summary This study of the 1973 Local Government Elections in England and Wales shows that the position of a candidate's name on the ballot paper can have an important effect in terms of the number of votes which he receives. In particular the lower‐placed members of each party are quite seriously disadvantaged. Investigations into the relationship between this positional effect and other aspects of the election show that it occurs quite generally. A simple model is formulated which attempts to explain the phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 3 publications
(2 reference statements)
0
24
0
1
Order By: Relevance
“…The topic is almost as old as the political science discipline itself (Bagley 1966;Brooks 1921;Dana 1912;Gold 1952;Mackerras 1968;Mueller 1969;White 1950;Wilson 1912), but scientific interest only really took hold in the last quarter of the twentieth century (Bakker & Lijphart 1980;Bowler et al 1992;Brook & Upton 1974;Byrne & Pueschel 1974;Darcy 1986;Darcy & McAllister 1990;Hughes 1970;Kelley & McAllister 1984;Lijphart & Pintor 1988;Miller & Krosnick 1998;Robson & Walsh 1974;Scott 1977;Taebel 1975;Volcansek 1981) and it has not lost momentum after the turn of the millennium (Alvarez et al 2006;Brockington 2003;Chen et al 2014;Faas & Schoen 2006;Geys & Heyndels 2003;Ho & Imai 2008;Johnson & Miles 2011;Kim et al 2015;King & Leigh 2009;Koppell & Steen 2004;Krosnick et al 2004;Lutz 2010;Matson & Fine 2006;Meredith & Salant 2013;Villodres & de la Puerta 2006 Darcy and McAllister 1990) review of the early literature, most studies do not address this problem, but simply measure whether candidates in different positions on average do better...…”
Section: What We Already Know About Ballot Position and Ballot Layoutmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic is almost as old as the political science discipline itself (Bagley 1966;Brooks 1921;Dana 1912;Gold 1952;Mackerras 1968;Mueller 1969;White 1950;Wilson 1912), but scientific interest only really took hold in the last quarter of the twentieth century (Bakker & Lijphart 1980;Bowler et al 1992;Brook & Upton 1974;Byrne & Pueschel 1974;Darcy 1986;Darcy & McAllister 1990;Hughes 1970;Kelley & McAllister 1984;Lijphart & Pintor 1988;Miller & Krosnick 1998;Robson & Walsh 1974;Scott 1977;Taebel 1975;Volcansek 1981) and it has not lost momentum after the turn of the millennium (Alvarez et al 2006;Brockington 2003;Chen et al 2014;Faas & Schoen 2006;Geys & Heyndels 2003;Ho & Imai 2008;Johnson & Miles 2011;Kim et al 2015;King & Leigh 2009;Koppell & Steen 2004;Krosnick et al 2004;Lutz 2010;Matson & Fine 2006;Meredith & Salant 2013;Villodres & de la Puerta 2006 Darcy and McAllister 1990) review of the early literature, most studies do not address this problem, but simply measure whether candidates in different positions on average do better...…”
Section: What We Already Know About Ballot Position and Ballot Layoutmentioning
confidence: 99%
“…Given the potential impact on the outcome of elections, it is not surprising that the potential effects of the candidates' position on the ballot paper have attracted considerable scholarly attention. The topic is almost as old as the political science discipline itself (Bagley 1966;Brooks 1921;Dana 1912;Gold 1952;Mackerras 1968;Mueller 1969;White 1950;Wilson 1912), but scientific interest only really took hold in the last quarter of the twentieth century (Bakker & Lijphart 1980;Bowler et al 1992;Brook & Upton 1974;Byrne & Pueschel 1974;Darcy 1986;Darcy & McAllister 1990;Hughes 1970;Kelley & McAllister 1984;Lijphart & Pintor 1988;Miller & Krosnick 1998;Robson & Walsh 1974;Scott 1977;Taebel 1975;Volcansek 1981) and it has not lost momentum after the turn of the millennium The more recent literature recognizes the problem and turns to experimental methods to deal with it. In the following we focus on such studies -which also include some early contributions -in order to assess the current knowledge of name order effects, to identify lacunae in the literature and to argue for the added value of our study.…”
mentioning
confidence: 99%
“…Many sucheffects have been documented to date (Becker, 1954;Belson, 1966;Brook & Upton, 1974;Carp, 1974;Mueller, 1970;Quinn & Belson, 1969 Payne, 1951;Rugg & Cantril, 1944;. Some of these demonstrations identified primacy effects, where response choices presentedearly were most likely to be selected.…”
Section: Studymentioning
confidence: 98%
“…Clearly, this property is unrealistic when some items are very similar or even substitutes for the others. Secondly, when it is applied to some real data, it was shown that it does not fit the data very well (see, for example, B6ckenholt, 1993;:Brook & Upton, 1974;and Tallis & Dansie, 1983). Therefore, to overcome these problems, dependency structures other than those in the Thurstone order-statistics models are required.…”
Section: Introductionmentioning
confidence: 99%